Undang-undang Republik Indonesia nomor 3 tahun 1975 tentang partai politik dan golongan karya : latar belakang beserta proses pembentukannya - Tambunan, A. (Binacipta, 1976)
On the law governing political parties and government-sponsored "functional groups" in Indonesia; includes text of the law.